Vitamin D status and relation with thyroid antibodies in patients with autoimmune thyroid disease - Khan, Hafsa Hassan; Amin, Md Feroz; Afsana, Faria; Hossain, Nazmul; Binte-Rouf, Rushda Sharmin (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: The most common cause of thyroid dysfunction is autoimmune thyroid disease (AITD), which includes Hashimoto's thyroiditis (HT) and Graves' disease (GD). Vitamin D insufficiency has been linked to autoimmune disorders, but the data are inconclusive. Objective: This study aimed to evaluate vitamin D status and its relation with thyroid autoantibodies (Anti-TPO-Ab, Anti-Tg-Ab, TRAb) in Bangladeshi patients with AITD. Material and methods: This case-control study was conducted in the department of Endocrinology in BIRDEM General Hospital from March 2022 to February 2024. Eighty newly diagnosed untreated AITD patients (40 HT, 40 GD), aged >18 years, were enrolled. Eighty subjects with normal thyroid function were recruited as controls. Serum 25(OH)D was checked by CMIA, and Anti-TPO-Ab, Anti-Tg-Ab, and TRAb were noted. The status of vitamin D was defined on serum 25(OH)D levels: sufficiency if ≥30ng/ml, insufficiency if 21-29ng/ml, and deficiency if ≤20 ng/ml. Results: It was observed that 67.5% of AITD cases (70.0% with HT, 65.0% with GD) had vitamin D deficiency, compared with 51.2% in controls (p=0.039). The mean 25(OH)D was significantly lower in patients with HT (13.22±8.89 ng/ml) and GD (14.46±9.73 ng/ml) than in controls (19.14±7.59 ng/ml) (p 0.001). Correlation analysis revealed that vitamin D was inversely related to Anti-TPO-Ab (r=-0.501, p=0.001 in HT and r=-0.431, p=0.006 in GD), Anti-Tg-Ab (r=-0.296, p=0.064 in HT; r=-0.299, p=0.061 in GD), and TR-Ab (r=-0.447, p=0.004), indicating that as vitamin D levels decrease, antibody titres tend to increase. Conclusion: Our findings indicate that patients with AITD have lower vitamin D levels. Since we found an inverse correlation between vitamin D and thyroid antibody levels, we may speculate that vitamin D deficiency can be one of the potential factors in the pathogenesis of AITD. [J Assoc Clin Endocrinol Diabetol Bangladesh, 2025;4(Suppl 1): S44]